'I'll do it step by step': care, cover and quiet campaigning. (February 2017) - McGuire, Darren; Lozada, Maria
This article explores a frontline account of care work and trade union organizing from the perspective of Maria Lozada, a care support worker and Filipino trade union organizer. Her testimony offers insight into life as a worker and organizer in the UK and highlights how migrants from outside the EU reflect upon immigration restriction and what it means for the quality of their employment relations and abilities to organize. The political and economic policy context within which the narrative is set is a move away from a demand-led UK immigration regime to further restriction for low-skilled work and immigration. Maria speaks about her role from a position of shelter, cover and anonymity, but is candid in her assessment of employers, policy changes and policymakers.